Dropsonde-Based Heat Fluxes and Mixed Layer Height over the Sea Surface near the Korean Peninsula - Min-Seong Kim; Byung Hyuk Kwon; Tae-Young Goo; Sueng-Pil Jung (Remote Sensing, 2022)
Dropsonde-based sensible heat flux, latent heat flux, and buoyancy flux were estimated over the sea around the Korean Peninsula in 2021. During a preceding severe weather (SW) mission, a total of 243 dropsondes were released from a National Institute of Meteorological Sciences (NIMS) Atmospheric Research Aircraft (NARA). The heat fluxes were indirectly validated by comparison with model-based heat fluxes. The sensible heat flux calculated by the bulk transfer method depended entirely on the temperature difference between the sea level and atmosphere, whereas the latent heat flux was mainly affected by wind speed. Boundary layer heights above 800 m are closely related to buoyancy flux, which is greater in regions with higher sea surface temperatures. Furthermore, the utility of the dropsonde was confirmed in the marine atmospheric boundary layer (MABL) growth, which is difficult to observe in situ and, a relationship was proposed for estimating MABL based on mean meteorological data over the sea level.